Mancha de phoma do cafeeiro: relação com irrigação, fertilidade do solo e nutrição de plantas - Dornelas, Gabriel Avelar (2017)
The phoma leaf spot (Phoma tarda) (PLS) is one of the main diseases of the crop, causing crop damage, due to leaf fall, dry branches and mummification of fruits, causing losses in production of up to 43%. Water supply and nutritional balance may affect the occurrence of the disease; such supply can be done via drip or sprinkler irrigation. Nowadays, little is known about the influence of mineral nutrition and soil fertility along the field space, especially with respect to K, P, B, Ca and Mn in the intensity of the disease. Thus, 3 experiments were carried out in the field, in order to verify the epidemiology and form of control for the phoma leaf spot using mineral nutrition and irrigation. In the 1oexperiment, the objective was to evaluate the interaction of rates of water with different doses of P2O5 (5 irrigation depths x 4 doses of P2O5) in the intensity of the coffee phoma stain. PLS evaluations were performed at 30-day intervals. The progress curve of the mean incidence of the PLS varied between the two evaluation years. In the first year, the peak of the disease occurred in August / 2012 (4.68%), already in the 2nd year, in September / 2013 (9.79%). There was interaction between doses of P2O5 and irrigation depths in the mean incidence of the PLS, being observed the increase of the disease with the increase of the irrigation slides up to the blade of 1.0 of Kc and in doses 80 to 240 kg ha-1 of P2O5. The exponential nonlinear model was adjusted in the 2 evaluated years. In the 2nd experiment, the interaction between K and B doses (4 K dosesx 4 doses of B) on the intensity of the PLS. Twenty-four evaluations were performed on coffee leaves at 30-day intervals. The mean progress curve of the incidence of PLS varied between the 2 years of evaluation. The peaks of the average incidence occurred on 06/16 and 09/13 of 2013 and 20/01 and 04/24 of 2014, respectively. In the year 2014, the incidence was lower compared to the year 2013, even with high load pending, possibly due to the higher temperatures recorded and occurring outside the normal period of the disease. There was a significant interaction between K and B doses with AACPI and AACPE, in which doses between 0 and 200 kg ha-1 of K at doses between 0 and 2 kg ha-1 of B showed the highest levels of disease And in the doses 0 to 100 kg ha-1 of K and 2 to 4 kg ha-1 of B the smallest leafing was observed. The objective of this study was to evaluate the spatial pattern of the relationship between PLS and plant nutrition in coffee plow irrigated by central pivot. There was spatial dependence of the PLS and the contents of P, K, Ca, B and Mn. The highest incidence of the PLS occurred in the areas with the lowest P and K contents and the highest B contents.